2024
DOI: 10.1161/atvbaha.123.320539
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Associated CD8 + T-Cells Are Not Activated Through Antigen-Mediated Interaction Inside Atherosclerotic Lesions

Maaike J.M. de Jong,
Frank H. Schaftenaar,
Marie A.C. Depuydt
et al.

Abstract: INTRODUCTION: Viral infections have been associated with the progression of atherosclerosis and CD8 + T-cells directed against common viruses, such as influenza, Epstein-Barr virus, and cytomegalovirus, have been detected inside human atherosclerotic lesions. These virus-specific CD8 + T-cells have been hypothesized to contribute to the development of atherosclerosis; however, whether they affect disease progression directly rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In this issue of ATVB, de Jong and colleagues 9 have looked deeper into the virus-specific T-cell responses in atherosclerosis and performed an immunopeptidomic analysis to identify virus epitopes. Sequencing of 10 carotid endarterectomy samples revealed that ≈2% of T-cell receptors matched virus-associated sequences.…”
Section: Immunopeptidomic Analysis Of Mhc-i From Atherosclerotic Plaquesmentioning
confidence: 99%
“…In this issue of ATVB, de Jong and colleagues 9 have looked deeper into the virus-specific T-cell responses in atherosclerosis and performed an immunopeptidomic analysis to identify virus epitopes. Sequencing of 10 carotid endarterectomy samples revealed that ≈2% of T-cell receptors matched virus-associated sequences.…”
Section: Immunopeptidomic Analysis Of Mhc-i From Atherosclerotic Plaquesmentioning
confidence: 99%